On-line integration of computer controlled diagnostic devices and medical information systems in undergraduate medical physics education for physicians - Hanus, Josef; Nosek, Tomas; Zahora, Jiri; Bezrouk, Ales; Masin, Vladimir (Physica medica, 2013)
We designed and evaluated an innovative computer-aided-learning environment based on the on-line integration of computer controlled medical diagnostic devices and a medical information system for use in the preclinical medical physics education of medical students. Our learning system simulates the actual clinical environment in a hospital or primary care unit. It uses a commercial medical information system for on-line storage and processing of clinical type data acquired during physics laboratory classes. Every student adopts two roles, the role of 'patient' and the role of 'physician'. As a 'physician' the student operates the medical devices to clinically assess 'patient' colleagues and records all results in an electronic 'patient' record. We also introduced an innovative approach to the use of supportive education materials, based on the methods of adaptive e-learning. A survey of student feedback is included and statistically evaluated. The results from the student feedback confirm the positive response of the latter to this novel implementation of medical physics and informatics in preclinical education. This approach not only significantly improves learning of medical physics and informatics skills but has the added advantage that it facilitates students' transition from preclinical to clinical subjects.
Keywords: Hearing Tests; ultrasonografie; Tomography, X-Ray Computed; Online Systems; biofyzika; lékaři; Biophysics; Ultrasonography; Physicians; Electrocardiography; krevní tlak; elektrokardiografie; elektronické zdravotní záznamy; on-line systémy; fyzika; Stents; zdravotnické prostředky; zrakové testy; systémová integrace; Education, Medical, Undergraduate; Systems Integration; sluchové testy; Vision Tests; Equipment and Supplies; Physics; studium lékařství pregraduální; Electronic Health Records; mikroskopie; Blood Pressure; Microscopy; stenty; počítačová rentgenová tomografie